1991
DOI: 10.1128/iai.59.4.1394-1401.1991
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of leukotoxin in leukotoxic and nonleukotoxic strains of Actinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans is a gram-negative bacterium that has been implicated in the etiology of several forms of periodontitis, especially localized juvenile periodontitis. A potent leukotoxin (Lkt) is produced by most A. actinomycetemcomitans isolates from patients with periodontal disease, but some isolates are leukotoxin nonproducing (Lkt-). The molecular bases for the differences in leukotoxin expression are being explored to clarify the role of leukotoxin in pathogenesis. We have previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
1
7

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 29 publications
(62 reference statements)
8
91
1
7
Order By: Relevance
“…It has been noted, however, that the main difference between clinical groups may not be the prevalence but rather the amount of putative pathogens found in positive samples (Gunsolley et al 1990). Leukotoxin production, a factor considered important for virulence of AA, varies significantly among strains of this species (Zambon et al 1983b, Kolodrubetz et al 1989, Spitznagel et al 1991, Brogan et al 1994). The strain-specific difference in leukotoxin production seems to be regulated at the level of transcription (Spitznagel et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted, however, that the main difference between clinical groups may not be the prevalence but rather the amount of putative pathogens found in positive samples (Gunsolley et al 1990). Leukotoxin production, a factor considered important for virulence of AA, varies significantly among strains of this species (Zambon et al 1983b, Kolodrubetz et al 1989, Spitznagel et al 1991, Brogan et al 1994). The strain-specific difference in leukotoxin production seems to be regulated at the level of transcription (Spitznagel et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Leukotoxin production, a factor considered important for virulence of AA, varies significantly among strains of this species (Zambon et al 1983b, Kolodrubetz et al 1989, Spitznagel et al 1991, Brogan et al 1994). The strain-specific difference in leukotoxin production seems to be regulated at the level of transcription (Spitznagel et al 1991). Brogan et al (1994) detected a 530 bp deletion in the promoter region of the leukotoxin operon and found that strains with this feature produced 10-20 times more leukotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Nonleukotoxic strains have been found to contain all four genes of the Itx gene cluster. Leukotoxin-positive strains produce two mRNA transcripts encoding Itx-CABD and ItxCA, whereas leukotoxin-negative strains produce lower levels of ltxCA and no ltx-CABD [52]. Therefore, toxin regulation appears to be at the level of mRNA transcription or stability.…”
Section: Leukotoxinmentioning
confidence: 99%
“…More recently, in an analysis of 17 strains of the organism, Brogan et al [51] have shown that the structure of the Itx promoter region of highly leukotoxic strains is similar and differs from that of non-leukotoxic strains. There is also evidence suggesting that leukotoxin production is under the control of environmental factors as it has been shown that the levels of Itx mRNAs are reduced in cells approaching the stationary phase of growth [52].…”
Section: Leukotoxinmentioning
confidence: 99%
See 1 more Smart Citation